ANALISIS PORTOFOLIO OPTIMAL BERDASARKAN CAPITAL ASSET PRICING MODEL DAN SINGLE INDEX MODEL PADA PERUSAHAAN IDX30 - Muhammad Wafa Aunillah (2021)
This research is a descriptive quantitative study that aims to look at diversification and determine the composition in the formation of an optimal portfolio of stocks that are consistently listed on the IDX30 Index in the period February 2017 - July 2021. By using the analysis of the Capital Asset Pricing Model (CAPM) and Single Index Model, and then look at the performance of the portfolio formed from the two methods, both of which have different results. The results of this study are: (1) in the CAPM method, obtained 2 stocks forming the optimal portfolio, namely: BBCA and ICBP. With a portfolio expected return level of 0.0026 or 0.26%, and a portfolio risk level of 0.0532 or 5.32%. (2) in the Single Index Model method, only one stock is obtained in the optimal portfolio, namely: BBCA. With an expected return portfolio of 0.0138 or 1.38%, and a portfolio risk level of 0.0057 or 0.57%. (3) CAPM portfolio performance has a Sharpe index value of 0.0485, a Treynor index of 0.0034, and a Jensen index of 0.00515. (4) the portfolio performance of the Single Index Model has a Sharpe index value of 2.4280, a Treynor index of 0.0154, and a Jensen index of 0.01690. (5) stock performance in CAPM, namely BBCA and ICBP shares with Sharpe indexes of 1.09286 and 0.17500, Treynor indexes of 0.00342 and 0.00319, and Jensen indexes of 0.00615 and 0.00116. (6) the performance of shares on SIM are BBCA shares, Sharpe index of 0.07857, Treynor index of 0.00025, and Jensen index of 0.00331.